Faktor-Faktor Pengembangan Karakter Kepemimpinan Calon Guru BK Fakultas Keguruan dan Ilmu Pendidikan - Aldhira Hanifah Azhar; Rury Muslifar; Wahyu Widyatmoko (Publikasi Indonesia, 2025)
This research aims to explore the factors influencing the development of leadership character among prospective guidance and counseling teachers at the Faculty of Teacher Training and Education, Mulawarman University. The study employs a qualitative research design with a descriptive approach. The data was collected from eight students from the Guidance and Counseling Study Program, spanning the years 2021 to 2024, using observation, interviews, and documentation techniques. The study identifies both supporting and inhibiting factors in leadership character development. Supporting factors include internal elements such as cognitive and affective aspects, and external factors including family, social, and academic environments. In contrast, inhibiting factors involve internal challenges like insecurity and lack of experience, and external barriers such as insufficient support from family or peers. The findings highlight that fostering self-confidence, engaging in positive social environments, and participating in extracurricular activities are crucial to developing leadership qualities. Implications for educational institutions include the need for targeted curricula and support systems to nurture these traits among future educators. This study provides practical recommendations for enhancing leadership skills in guidance and counseling programs.